Regulatory Influence on the Overall Quality of Platform Work: Lessons from the Chilean Context - Bellido de Luna-Mayea, D (SAGE Publications Ltd, 2024)
This study examines the impact of Chile’s new regulation (Act N° 21.431) on the quality of platform work via 23 detailed interviews with gig workers and trade unionists. It reveals that regulation helped but fell short in its attempts to enhance job quality in the platform economy. By providing empirical evidence on the efficacy of regulation, this article enriches the discourse on platform work regulation, while offering a nuanced understanding of the pitfalls of new legislation, delivering key insights for shaping national labour policies. This contribution is central for policymakers aiming to navigate the complexities of regulating platform work and ensuring meaningful improvements in job quality. © The Author(s) 2024.